Hyalinizing trabecular adenoma of thyroid - a case report and review of literature (Bangladesh Journal of Otorhinolaryngology, 2012)
Hyalinizing trabecular adenoma of thyroid is a rare tumour first described in 1987. Its cytological and histopathological features are very close to other thyroid neoplasms specially papillary and medullary carcinoma. So misinterpretation of cytological feature may lead to a total thyroidectomy whereas a lobectomy is enough to cure this benign condition. Here we present such a case in a 30-year-old female patient and review the diagnosis and management DOI: http://dx.doi.org/10.3329/bjo.v18i2.12018 Bangladesh J Otorhinolaryngol 2012; 18(2): 203-206